Evaluation of library portals of Iranian governmental Universities in 2013 - Mohsen Nowkarizi; Akram Koochaki (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2015)
Purpose: Iranian (state) university library portals were investigated with the aim of determining their status. Methods: The population of the research included 58 Iranian university (state) library portals. The data collection tools were questionnaire and the researcher-made checklist which was designed in terms of 145 items and 9 general area include "Information Retrieval ", "Public and Information Services", "Quality of Writing", "Accessibility", "Personalization", "Content Management", "Organization", "Protection and Security" and "Management Facilities of Portal in Public Library Services" that after the validity and reliability testing, a simple random sampling method was used for data collection and the sample size was determined 40 portals based on the Cochran formula. Finding: The results indicated that generally in the university library portals related to the Ministry of Science, Research and Technology in terms of utilization of the component of the examined areas in this research. In all cases, the society average significantly was in the good level and it was desirable. Also, the portals of 13 universities were in desirable level, 24 ones in good level and 3 others in average level. The examined dimension in the "Quality of Writing" and “Accessibility” areas was in the desirable status and it was good in the areas of  "Information Retrieval", "Public and Information Services", "Personalization", "Content Management", "Organization", "Protection and Security" and " Management Facilities of Portal in Public Library Services". The "Management Facilities" with the average score of 3.61 and the "Quality of Writing" with 4.58 have respectively gained the minimum and maximum scores. It seems that due to the existing substructures in the portal, there is a suitable context for presenting more and more services and facilities to the members thorough it. In fact, move from website to portal also indicates that the librarians have recognized the need to change the website to the portal.